The antioxidant and pro-oxidant activity of vitamin C and trolox in vitro: a comparative study - Poljšak, Borut; Raspor, Peter (Journal of applied toxicology, 2008)
The antioxidant and pro‐oxidant properties of ascorbic acid (vitamin C) and the water‐soluble analogue of α‐tocopherol (trolox) were compared. Trolox has advantages over α‐tocopherol, the latter being only lipid‐soluble due to the presence of a carboxyl group in lieu of a phytol chain which imparts trolox with water solubility. Trolox is used as a standard antioxidant in biochemical studies against which the antioxidant capacity of compounds is compared. Although ascorbic acid and tocopherols possess strong antioxidant properties, they might also exhibit pro‐oxidant properties in the presence of free transition metals. Thus, reactions detailed in this study were performed in the presence of Cr(VI) in an effort to investigate the potential of ascorbic acid and trolox to generate hydroxyl radicals in a Fenton‐like reaction. Results obtained were derived from reactions containing the same concentration of ascorbic acid and trolox under identical experimental conditions. Hydroxyl radical formation was observed in the reaction of Cr(VI) with ascorbic acid resulting from ascorbic acid auto‐oxidation and H2O2 formation. Hydroxyl radical formation was only detected in the reaction mixture containing Cr(VI) and trolox following the addition of H2O2. Copyright © 2007 John Wiley & Sons, Ltd.